Feeding habits of juvenile Centropomus robalito (Centropomidae: Actinopterygii) in Barra de Navidad lagoon, Mexican Central Pacific - Flores Ortega, Juan Ramon (2015)
In America, the species of genus Centropomus (Snooks) are a key component of the tropical estuarine ichthyofauna. These species use brackish water bodies mainly as nursery areas, although adult specimens are also present. The Yellow-fin snook Centropomus robalito (Jordan & Gilbert, 1882) is one of the most abundant species in the coastal wetlands of the Mexican Central Pacific but there is very few data on its biology. The goal of this research was to analyze the diet composition of juvenile specimens of C. robalito and to study its ontogenic changes in Barra de Navidad coastal lagoon located in the Mexican Central Pacific. Specimens were collected between January 2011 and March 2012 using several fishing gears (cast net, gillnets and beach purse seine). A total of 681 juvenile fish were obtained and classified in three size-classes (small < 69 mm TL; intermediate 70-139 mm TL; large ≥ 140 mm TL) to analyze stomach contents. The number of stomachs with some content was 292, and the general diet composition included 14 food items dominated by crustaceans (Alpheidae, Penaeidae, Brachyura) and fishes (Gobiidae, Engraulidae, Mullidae), with minor representation of copepods and insects. Significant changes in the diet composition between size-classes were found. Diet of small and intermediate fish was dominated by juvenile peneid shrimps, and fishes (mainly Gobiidae); while for larger fish, Alpheidae shrimps, and in second place, fish from Engraulidae and Mullidae were dominant in the diet. It is concluded that C. robalito is a generalist species with ontogenic changes in its diet.